Synthesis and Molecular Modeling of 1,2,4 Triazole-Based Sulfanilamide Derivatives Using Dual Tail Strategy as Possible CAIs with their Cytotoxic Evaluation - Al-Nakeeb, Mayada R.; Mohammed, Mohammed Hassan (Journal of Contemporary Medical Sciences, 2025)
Objective: The aim of the study was to design and synthesize a novel series of 1,2,4 triazole-based sulfanilamide derivatives targeting carbonic anhydrase IX (CA IX), a promising therapeutic target in cancer, using dual tail approach, and to assess their cytotoxic effect against breast and colon cancer cell lines. Methods: The final compounds P1-P6 were synthesized starting from sulfanilamide. Characterization of their structure was performed using FT-IR, NMR and ESI-MS spectroscopies. Cytotoxic evaluation of the six derivatives was performed against breast and colon cancer cell lines compared to acetazolamide (AZM). In addition, molecular docking was conducted with CA II, CA IX and CA XII to compare fitting of the derivatives with zinc ion. Results: This study showed that compound P5 had a potential cytotoxic effect against cancerous cell lines. Performing molecular docking revealed that P5 had good zinc binding interaction with CA IX compared with CA II and CAXII, indicating possible selectivity for CA IX. Conclusion: According to the molecular docking and cytotoxic evaluation, compound P5 could be a promising CA IX inhibitor using the dual tail approach to improve selectivity against this isoform.